The Impact of Intellectual Capital, Islamic Corporate Governance, and Zakat Disclosure on the Financial Performance of Islamic Commercial Banks in Southeast Asia - Nasution, Qisti Marhamah; Haryono, Slamet (Economica: Jurnal Ekonomi Islam, 2023)
Islamic commercial banks play a vital role in Southeast Asia’s financial sector, adhering to sharia principles that shape banking operations and performance. This study examines the impact of intellectual capital (VACA, VAHU, STVA), Islamic corporate governance (BOD, AC, BOC, DPS), and zakat disclosure (ZD) on financial performance. Using a quantitative approach, it analyzes secondary panel data from 2016–2022, with 81 observations, employing EViews 10. The findings reveal that VACA, STVA, BOD, AC, BOC, and DPS have no significant impact on financial performance. However, VAHU positively affects financial performance, while ZD has a significant negative effect. Collectively, all independent variables significantly influence financial performance, with an R² of 48%, indicating that 48% of financial performance is explained by these factors, while 52% is influenced by others. These results emphasize the importance of human capital efficiency and zakat transparency in shaping financial performance. Governance structures may require further refinement to enhance their impact. Future research should explore additional variables, extended study periods, and alternative methodologies to deepen the understanding of financial performance drivers in Islamic commercial banking.